A review of Backward-Facing Step (BFS) flow mechanisms, heat transfer and control. (June 2018) - Chen, Lin; Asai, Keisuke; Nonomura, Taku; Xi, Guannan; Liu, Tianshu
Highlights: Backward-Facing Step (BFS) separation flow and heat transfer models summarized. Theoretical, experimental, numerical studies analyzed for separation/reattachment. Control laws and methods summarized from multi-disciplinary research works. Future trends, challenges and possible innovations put forward. Abstract: Backward-Facing Step (BFS) flow is one representative model for separation flows, which can be widely seen in aerodynamic flows (airfoil, spoiler, high attack angle process), engine flows, condensers, vehicles (cars, boat), heat transfer systems, and even the flow around buildings, etc. The flow separation after a simple stage will introduce separation bubble formation, evolution and re-attachment process, which is dependent on the BFS geometric design, the inlet and outlet conditions, turbulent intensity, as well as heat transfer conditions. In the past decades, it has been widely studied by various theoretical, experimental and numerical methods. Considering the importance of BFS flow in both theoretical and engineering aspects, this paper is focused on a review study of BFS flows from fundamental understandings to various experimental and numerical developments in a historical viewpoint. Basic models and the parameter-based after-step flow laws are summarized and categorized in this study. It is shown that the step size (duct expansion ratio) will define the basic re-circulation and re-attachment process, while the coupled effects of inflow parameters and the perturbation designs also help shape the flow behaviors after BFS. The review is also extended with model generalizations and the implications on system design, especially the heat transfer effects and the representative control designs are discussed in detail. Future trends and prospects in BFS studies are also included in this study.